Inpatient dermatological consultations in a university hospital - Suzana Mancusi; Cyro Festa Neto (Clinics, 2010)
INTRODUCTION: Dermatology is primarily an outpatient specialty, but it also plays an important role in the care of inpatients. METHODS: We conducted a prospective study that recorded data from inpatient dermatology consultation request forms over a period of four months. The study evaluated 313 requests that led to 566 visits, 86 biopsies, 35 laboratory exams, 41 direct microscopic studies, 18 direct immunofluorescence analyses, 14 skin cultures and a few other exams. RESULTS: The most frequent requesting service was internal medicine (24%), followed by neurology (12%), cardiology (11%), infectious diseases and pediatrics (8% each) and psychiatry and general surgery (6% each). The most frequent diagnostic groups were infectious diseases (25%, divided into fungal infections (13%), bacterial infections (7%) and viral infections (5%)), eczemas (15%) and drug reactions (14%). To our knowledge, this is the first study to attempt to evaluate the impact of the consultations by asking multiple-choice questions that were analyzed by the authors. In 31% of the cases, the consultation was considered extremely relevant because it aided in managing the disease that led to admission or treated a potentially severe dermatological disease. In 58% of the cases, the consultation was considered important because it facilitated diagnosis and/or treatment of a dermatological disease that was unrelated to the reason for admission.